The Political Background to the Establishment of the Slavic Nomocanon in the Thirteenth Century - Koprivica, Marija (Studies in church history, 2020)
The first collection of canon law translated from the Greek into the Slavic language in the ninth century supported the consolidation of Christianity among the Slav peoples. This article focuses on the nomocanon of St Sava of Serbia (Kormchaia), a collection which was original and specific in its content; its relationship to other contemporary legal historical documents will be considered. The article also explores the political background to the emergence of Orthodox Slav collections of ecclesiastical and civil law. The political context in which these collections originated exercised a determinative influence on their contents, the selection of texts and the interpretation of the canons contained within them. The emergence of the Slavic nomocanon is interpreted within a context in which Balkan Slav states sought to foster their independence and aspired to form autocephalous national churches.